In silico study: Candidate compounds of Jatropha curcas L. plant as breast cancer inhibitors - Desti Amalia Ramadhayanti; Moh Mirza Nuryady (Green and Tropical Laboratory for Sustainability, 2025)
Background: Cancer is a disease caused by the growth of abnormal cells in the body, which can grow and attack any part of the body. When someone has cancer, the microRNAs in the body play a role in preventing cancer from multiplying. Therefore, inhibiting microRNAs could be a solution for developing cancer drugs. One plant that can be used as a natural chemotherapy agent is Jatropha curcas L., also known as the castor oil plant. Objectives: Jatropha curcas plants can be used as an alternative to petroleum, namely in the manufacture of biodiesel and as a raw material for treating diseases including cancer, skin diseases, respiratory diseases, and infectious diseases. Methods: The research method is the 3D structure of Sirtulin1 protein (pdb id: 4I5I), β-sitosterol and 2-(Hydroxymethyl)-2 nitro-1,3-propanediol prepared with the PyRx program. Molecular docking was analyzed by the interaction of β-sitosterol and 2-(Hydroxymethyl)-2 nitro-1,3-propanediol with Sirtulin1 protein using Autodock 4.2 software. and visualized with discovery studio version 4.1. Data analysis used descriptively. Results: The results of the study of β-sitosterol and 2-(Hydroxymethyl)-2 nitro-1,3-propanediol with sirtulin1 protein produced 12 amino acid residues in the form of SER275, ASN465, SER442, ASP272, GLU467, PHE321, CYS380, ARG384, ILE387, PHE321, PHE366, PHE388. The presence of this bond indicates that the test ligand can bind to the amino acids present in the Sirtulin1 protein. Conclusion: Based on the docking results, it is known that the bonds that occur in the 2-(Hydroxymethyl)-2 nitro-1,3-propanediol ligand and the Sirtulin1 protein are Conventional Hydrogen Bond and Carbon Hydrogen Bond bonds. Hydrogen bonds are the strongest bonds among covalent bonds so they are more widely distributed and produce pharmacological activity. Thus, compounds that have amino acid residues in the form of hydrogen bonds are stronger and produce high inhibitory activity. The presence of these bonds indicates that the test ligand can bind to the amino acids in the Sirtulin1 protein.